Boosting laboratory photoelectron spectroscopy by megahertz high-order harmonics. (20th January 2015) - Chiang, Cheng-Tien; Huth, Michael; Trützschler, Andreas; Kiel, Mario; Schumann, Frank O; Kirschner, Jürgen; Widdra, Wolf
Abstract: Since the discovery of the photoelectric effect, photoelectron spectroscopy has evolved into the most powerful technique for studying the electronic structure of materials. Moreover, the recent combination of photoelectron experiments with attosecond light sources using high-order harmonic generation (HHG) allows direct observation of electron dynamics in real time. However, the efficiency of these experiments is greatly limited by space-charge effects at typically low repetition rates of photoexcitation. Here, we demonstrate HHG-based laboratory photoemission experiments at a photoelectron count rate of 1 × 10 5 electrons/s and characterize the main features of the electronic band structure of Ag(001) within several seconds without significant degradation by the space-charge effects. The combination of a compact HHG light source at megahertz repetition rates with the efficient collection of photoelectrons using time-of-flight spectroscopy may allow rapid investigation of electronic bands in a flexible laboratory environment and pave the way for an efficient design of attosecond spectroscopy and microscopy.